Electronically reconfigurable two-path fractional-order PI/D controller employing constant phase blocks based on bilinear segments using CMOS modified current differencing unit. (April 2019) - Sotner, Roman; Jerabek, Jan; Kartci, Aslihan; Domansky, Ondrej; Herencsar, Norbert; Kledrowetz, Vilem; Alagoz, Baris Baykant; Yeroglu, Celaleddin
Abstract: This work introduces a versatile type of electronically controllable bilinear transfer segments, i.e. two ports allowing independent electronic control of zero and pole of transfer function, based on modified current differencing unit (MCDU) active element. These proposed bilinear transfer segments serve for construction of fractional-order constant phase block ( φ α = ±15° and ±36°, i.e. orders α = ±1/6 and ± 2/5, tested in our case) representing electronically controllable integrator or differentiator (in dependence on current demand) as a part of novel two-path system of the fractional-order proportional-integral or derivative (FOPI/D) controller. The example of design procedure employs four bilinear transfer segments, electronically controllable proportional path and summing stage. Cadence IC6 Spectre simulation results (TSMC 0.18 μm CMOS process) in both frequency and time domain are performed in order to confirm expected behavior of the system. An application of the proposed FOPI controller in control of linear voltage regulator is also demonstrated and performance improvements of the proposed design are discussed.